CUSTOMER CHURN PREDITION IN TELECOM SECTOR USING SUPPORT VECTOR MACHINE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Acquisition and retention of new clients are one of the most significant concerns ofbusinesses. While recipient companies concentrate on acquiring new customers, mature onestry to focus on retention of the existing ones in order to provide themselves with theopportunity of cross – selling. According to Freeman (1999) one of the most significant waysof increasing customers’ value is to keep them for longer period of time.